ANALYSIS OF CRIMINAL SANCTIONS FOR SELLERS OF PRIVATE PORNOGRAPHIC CONTENT ON SOCIAL MEDIA - Itok Dwi Kurniawan (Pojok Publisher, 2024)
One of the problems related to internet abuse is the spread of pornographic content. The purpose of writing this article is to determine the form of accountability for perpetrators of criminal acts of spreading pornographic content on social media. This article was written using normative legal research methods with a statutory approach. The results of this research are related to the criminal act of distributing pornographic content, the Government of the Republic of Indonesia has issued several related laws and regulations. Some of these regulations include Law Number 1 of 2023 concerning the Criminal Code, Law Number 44 of 2008 concerning Pornography, Law Number 11 of 2008 concerning Information and Electronic Transactions which have been passed 2 (two) times change. All of these laws have provided strict sanctions for perpetrators of spreading pornographic content because they have violated moral norms, in addition to violating legal norms.